The Impact of Corona Virus on the Socio-Economic Life of Nigerians - Hope Ikwe (Culture e Studi del Sociale)
Corona Virus Disease (COVID-19) is an infectious disease caused by a newly discovered corona virus that can be transmitted through droplets from cough and sneeze. People who are infected can experience mild to moderate symptoms and can recover without requiring special treatment. However, aged patients and those with respiratory disease can develop serious illness. Maintainence of high standard of hygiene through frequent washing of hand, use of hand sanitizer and social distancing has been recommended as ways of slowing down the transmission of this disease that has been declared a global health emergency.This study examines how the coronavirus pandemic which is sweeping around the globe affects the socio-economic life of Nigerians. The study reveals that the effect of the pandemic on the socio- economic life of Nigerians is enormous due to the peculiarity of the Nigerian system and economy which depends on close social contact that hinges on the theory of communitarianism,a theory that supports the fact that a person’s personality or identity is molded by the society. Hence, a total lock down in Nigeria is not sustainable over a long period of time.